Existence and multiplicity results for non-autonomous second-order Hamiltonian systems - Liu Chungen; Zhong Yuyou (Advances in Nonlinear Analysis)
In this article, using the least action principle and minimax methods in critical point theory, some existence and multiplicity results for periodic solutions of second-order Hamiltonian systems are obtained.